Determinación de los Gases Contaminantes en Fuentes Fijas en la Empresa de Cereales la Pradera y la Institución Pública del Hospital General de Latacunga. - Lidioma Lomas, Margarita Paulina (2018)
The possible atmospheric pollution generated by Cereales la Pradera Company and the Public Institution of the General Hospital in Latacunga Canton. For the determination the pollution gases concentration was the purpose of this research, constant measurements were made with the TESTO 350 Combustion Gas Analyzer that evaluated the O2, CO2, CO, NOx, SO2 gases, according to the international (USEPA) United States Environmental Protection Agency where the monitoring and evaluation protocols established in TULSMA, Book VI, Annex 3, are governed. This research was conducted during a year and was divided into two parts to meet the objectives set; in the first part a diagnosis of the study areas was carried out, which included interviews to the maintenance managers to know the current environmental problems that were evidenced in the monitoring and in the second part, with the information collected in the field was obtained the following results: NOx 89.325 mg/Nm3 and SO2 12.002 mg/Nm3 at the General Hospital of Latacunga and in the company of cereals the Prairie: NOx 121.636 mg/Nm3, SO2 13.442 mg/Nm3, NOx 120.957 mg/Nm3 and SO2 44.563 mg/Nm3 in their cauldrons 1 and 2 respectively the same as were compared with the environmental regulations in force by the Graphical analysis it was shown that there is minimal variations during the days monitored. The data obtained in the atmospheric monitoring at the General Hospital of Latacunga and Prairie Grain Company generates information for decision making in environmental policies at the enterprise level; these policies include constant monitoring, timely maintenance, and regulatory compliance and avoid penalties, with the aim of improving the environmental quality of the air of the city.